(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the main idea, the scope of the subject, and the uniqueness of the poetic style of Lutfi, a major representative of Uzbek classical literature. Views are expressed on the Sufi content underlying the poetic images such as the face, the face, and the eyes used in the poet’s lyrics, as well as the expression of various metaphors and similes. The article serves to reveal the place, value, and significance of Lutfi’s lyrics in Turkish classical poetry.